Impact of a pilot multimodal intervention to decrease antibiotic use for respiratory infections in a geriatric clinic. Issue 1 (10th January 2022) - Chauhan, Lakshmi R.; Huang, Misha; Abdo, Mona; Church, Skotti; Fixen, Danielle; MaWhinney, Samantha; Miller, Matthew; Erlandson, Kristine M.
Abstract: Background: More than 80% of antibiotics are prescribed in the outpatient setting, of which 30% are inappropriate. The National Action Plan for Combating Antimicrobial Resistance called for a 50% decrease in outpatient antibiotic use by 2020. Inappropriate antibiotics are associated with adverse reactions and Clostridioides difficile infection, especially among older adults. Study design: Before and after study. Methods: We performed a quality improvement initiative at the University of Colorado Seniors Clinic. Providers received education on antibiotic guidelines, electronic antibiotic order sets were introduced with standardized stop dates. Antibiotic use data were collected for 6 months before and 6 months after the intervention, from December to May to avoid seasonal variation. Descriptive statistics and linear mixed-effects regression models were used for this comparison. Results: Total antibiotic prescriptions for acute respiratory conditions decreased from 137 prescriptions before the intervention (December 1, 2017, to May 31, 2018) to 112 prescriptions after the intervention (December 1, 2018, to May 31, 2019), driven primarily by decreases in antibiotic prescriptions for pneumonia, sinusitis, and bronchitis. Prescriptions for broad-spectrum antibiotics declined following the intervention including decreases in levofloxacin from 12 (9%) to 3 (3%) and amoxicillin-clavulanate from 15 (12%) to 7 (7%). We detected significant reductions in prescribed antibiotic durations (days) after the intervention for sinusitis (estimate, −2.0; 95% CI, −3.1 to −1.0; P = .0003), pharyngitis (estimate, −2.5; 95% CI, −4.6 to −0.5; P = .018), and otitis (−3.2; 95% CI, −5.2 to −1.3; P = .008). Conclusions: Low-cost interventions were initially successful in changing patterns of antibiotic use and decreasing overall antibiotic prescribing among older patients in the outpatient setting. Long-term follow-up studies are needed to determine the sustainability and clinical impact of these interventions.